KAJIAN RHIZOCTONIA BINUKLEAT SEBAGAI MIKORIZA DAN PERANANNYA DALAM MENINGKATKAN KETAHANAN BIBIT VANILI (VANILLA PLANIFOLIA ANDREWS) TERHADAP CEKAMAN KEKERINGAN - , HARYUNI, Prof. Dr. Ir. Bambang Hadisutrisno, DAA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Vanilla (Vanilla planifolia Andrews) cultivation in Indonesia is often suffer from prolonged drought. One of the attempts to increase resistance of vanilla plants to drought stress by inoculating with mycorrhiza fungi. The objective of this research was to examine the ability of binucleate Rhizoctonia (BNR) as mycorrhiza fungi to increase the growth, resistance to drought stress, and health of vanilla seedlings. In this study, the characterization and identification of BNR with polyphasic (combine) method were also conducted. The result showed that the BNR SR-8 isolate tested were mycorrhiza fungi in the root zone and could cause, physiological changes, increase plant growth, the resistance, and health of vanilla seedlings to drought stress. BNR SR-8 isolate belonged to Ceratobasidium sp. (anamorphous. binucleate Rhizoctonia AG-F group).